Exploring the heterogeneity in community pharmacist-led medication review studies: a systematic review - Vogt, Cathrin; Möcker, Robert; Jacke, Christian O.; Haefeli, Walter E.; Seidling, Hanna (Research in social and administrative pharmacy, 2024)
BACKGROUND: Findings on the effectiveness of medication reviews led by community pharmacists (CPs) are often inconclusive. It has been hypothesized that studies are not sufficiently standardized, and thus, it is difficult to draw conclusions. - OBJECTIVE(S): To examine differences in the way CP-led medication review studies are set up. This was accomplished by investigating (1) patient selection criteria, (2) components of the medication review interventions, (3) types of outcomes, and (4) measurement instruments used. - METHODS: A systematic literature search of randomized controlled trials of CP-led medication reviews was carried out in PubMed and Cochrane Library. Information on patient selection, intervention components, and outcome measurements was extracted, and frequencies were analyzed. Where possible, outcomes were mapped to the Core Outcome Set (COS) for medication review studies. Finally, a network analysis was conducted to explore the influence of individual factors on outcome effects. - RESULTS: In total, 30 articles (26 studies) were included. Most articles had a drug class-specific or disease-specific patient selection criterion (n = 19). Half of the articles included patients aged ≥60 years (n = 15), and in 40% (n = 12/30) patients taking 4 drugs or more. In 24 of 30 articles, a medication review was comprised with additional interventions, such as distribution of educational material and training or follow-up visits. About 40 different outcomes were extracted. Within specific outcomes, the measurement instruments varied, and COS was rarely represented. - CONCLUSION: The revealed differences in patient selection, intervention delivery, and outcome assessment highlight the need for more standardization in research on CP-led medication reviews. While intervention delivery should be more precisely described to capture potential differences between interventions, outcome assessment should be standardized in terms of outcome selection by application of the COS, and with regard to the selected core outcome measurement instruments to enable comparison of the results.
Gesehen am 26.11.2024